International rules on health data sharing for a new pandemic agreement - Anna Holzscheiter; Maria Weickardt Soares (German Institute of Development and Sustainability (IDOS), 2024)
The negotiations on the Pandemic Agreement offered a key opportunity for the World Health Organization's (WHO) 194 Member States to address the weaknesses of existing international regulations governing global health - and to adopt a new legal instrument at the Seventy-seventh World Health Assembly in May 2024. However, Member States were not able to successfully conclude the negotiations. Between late 2021 and May 2024, an Intergovernmental Negotiating Board (INB) had been working on finding a postCOVID-19 consensus on a long list of issues related to pandemic preparedness, surveillance and response. Yet, the high hopes of many WHO Member States as well as non-state actors had given way to sober realism. The failure to reach a consensus, and to do so by the planned deadline, which was very ambitious, can be interpreted in various ways. From the point of view of diplomatic efforts as an 'investment', these efforts may be framed as a 'waste of time'. From the perspective of substantial controversies, the decision to prolong the debate may allow for the necessary space to adopt a widely endorsed international agreement.
Keywords: 320; pandemic preparedness; Covid-19; Pandemic Treaty; Pandemic Agreement; global health equity; health data; health data sharing; benefit sharing in health; international health law